2015
DOI: 10.1107/s2053230x14026843
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive review of the lipid cubic phase orin mesomethod for crystallizing membrane and soluble proteins and complexes

Abstract: The lipid cubic phase or in meso method is a robust approach for crystallizing membrane proteins for structure determination. The uptake of the method is such that it is experiencing what can only be described as explosive growth. This timely, comprehensive and up-to-date review introduces the reader to the practice of in meso crystallogenesis, to the associated challenges and to their solutions. A model of how crystallization comes about mechanistically is presented for a more rational approach to crystalliza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
251
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 238 publications
(253 citation statements)
references
References 92 publications
(142 reference statements)
2
251
0
Order By: Relevance
“…To understand the structureactivity relationship around the chemical series for the A 2A R and facilitate further optimization, we sought to obtain the crystal structure of the A 2A R in complex with Cmpd-1. Although a number of crystal structures of A 2A R bound to various antagonists and agonists have been reported (7)(8)(9)(10)(11)(12)(13)(14) using lipidic cubic phase (LCP) methods (15,16), we were unable to obtain high-quality crystals of A 2A R bound to Cmpd-1. As an alternative approach we obtained a 3.5-Å resolution crystal structure of A 2A R in complex with Cmpd-1 by using a BRIL fusion construct and performing the crystallization in vapor-phase diffusion in the detergent lauryl maltose neopentyl glycol (LMNG).…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…To understand the structureactivity relationship around the chemical series for the A 2A R and facilitate further optimization, we sought to obtain the crystal structure of the A 2A R in complex with Cmpd-1. Although a number of crystal structures of A 2A R bound to various antagonists and agonists have been reported (7)(8)(9)(10)(11)(12)(13)(14) using lipidic cubic phase (LCP) methods (15,16), we were unable to obtain high-quality crystals of A 2A R bound to Cmpd-1. As an alternative approach we obtained a 3.5-Å resolution crystal structure of A 2A R in complex with Cmpd-1 by using a BRIL fusion construct and performing the crystallization in vapor-phase diffusion in the detergent lauryl maltose neopentyl glycol (LMNG).…”
mentioning
confidence: 86%
“…The LCP method for membrane protein crystallogenesis (15,16) has been used successfully to crystallize a number of GPCRs over the past several years and has become the method of choice; this is exemplified by the fact that 38 of the 39 GPCRs with structures reported have been successfully crystallized in LCP. Therefore, we initially attempted to crystallize A 2A R in complex with Cmpd-1 in LCP.…”
Section: Significancementioning
confidence: 99%
“…Currently, amphipols gained significant popularity in the Cryo-EM field [37][38][39] but also in solution NMR studies [40,41]. For the X-ray crystallography field, it has been shown that amphipols are compatible with lipidic cubic phases [42], thus currently amphipols can only be used for in meso crystallization [43], similarly to SMALPs. There are several other approaches developed (and being actively developed) for the stabilization of membrane proteins, including nanodiscs [44], calixarens [45], fluorinated surfactants [46] and others, but they are beyond the scope of this mini-review.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the majority of GPCR structures have been solved using LCP crystallization (for a comprehensive review, see Caffrey, 2015). In this method, the receptor is crystallized in a lipidic environment instead of from a detergent solution.…”
Section: Molecular Biology Approaches To Facilitate Gpcr Crystallographymentioning
confidence: 99%
“…Furthermore, the discovery of new detergents for protein solubilization (Chae et al, 2010;Cho et al, 2015), the development of novel crystallization techniques such as lipidic cubic phase (LCP) crystallization (Caffrey, 2015), and key advances in several aspects of crystallography, such as microcrystallography , X-ray free electron lasers (XFELs), and serial femtosecond crystallography (SFX) have also contributed decisively to the field of GPCR structural biology.…”
Section: Introductionmentioning
confidence: 99%